3D printing of immediate-release tablets containing olanzapine by filaments extrusion. (3rd August 2021) - Bhatt, Ukti; Malakar, Tushar Kanti; Murty, Upadhyayula Suryanarayana; Banerjee, Subham
Abstract: In this work, hot-melt extrusion (HME) is coupled with fused deposition modeling (FDM) mediated 3D printing to demonstrate additive manufacturing to fabricate immediate release (IR) prototypes of olanzapine with the aim of enhanced solubility using a fast disintegrating polymer (Kollicoat ® IR). Drug-polymer solubility and interaction parameters were estimated by Hansen solubility parameters and Hildebrand–Scott equation. The obtained values signified drug–polymer miscibility. The detailed in vitro physicochemical evaluations of the developed filament through HME and its derived 3D printed tablet by FDM technique were assessed thoroughly by several analytical means such as light microscopy, DSC, XRD, FT-IR, SEM, etc. The average disintegration time of this developed 3D printed IR tablet was found to be 63.33 (±3.6) sec complying with the USP limit. Additionally, in vitro dissolution study data revealed almost close correlations and both showed 100% of drug release within 15 min, thus complying with the definition of IR tablet. Thus, this study demonstrates the feasibility of directly using olanzapine-Kollicoat ® IR through the HME process without the addition of any plasticizers, organic solvents, etc. and coupling of HME with 3D printing technology allowing prototypes of IR tablet of olanzapine.